Primary carcinoid tumor arising within mature teratoma of the kidney: report of a rare entity and review of the literature - Parwani Anil V; Armah Henry B (BMC, 2007)
Abstract Background Primary carcinoid tumor arising within mature teratoma of the kidney is extremely rare, and their clinicopathologic features are not well described. Our objective was to further define the clinical features and pathologic spectra of primary carcinoid tumor arising within mature teratoma of the kidney. Methods Six previously reported case reports were identified using MEDLINE and a subsequent bibliographic search of all pertinent reports and reviews was performed. We also searched the electronic medical archival records of our institution and identified one additional unreported case. Data were extracted on the demographics, predisposing factors, clinical presentation, radiographic features, gross pathology, microscopic pathology, immunophenotype, therapy, and outcome of each of these seven cases. Results Primary carcinoid tumor arising within mature teratoma of the kidney was found at a mean age of 41.4 years. Of the 7 cases, 3 were female and 4 were male. Two of the 7 cases (28.6%) were associated with horseshoe kidney. It typically presented with abdominal pain without carcinoid syndrome. It typical radiologic appearance was well circumscribed partly calcified Bosniak II-III lesion. Histologically, the carcinoid tumor showed monotonous small round cells arranged in classic anastomosing cords/ribbons intermixed with solid nests. Surgery was curative, no additional treatment was required, no local recurrences occurred, and no metastases occurred in all 7 cases. The 3 cases with available outcome data were alive at the time of publication of their respective cases (mean, 5 months). Conclusion Primary carcinoid tumor arising within mature teratoma of the kidney is a rare tumor that typically presents with abdominal pain without carcinoid syndrome. It is not associated with local recurrence and metastasis, is surgically curable, and has excellent prognosis.